2017
DOI: 10.1042/bsr20160542
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-379 inhibits the proliferation, migration and invasion of human osteosarcoma cells by targetting EIF4G2

Abstract: Osteosarcoma (OS) is an aggressive malignant mesenchymal neoplasm amongst adolescents. The aim of the present study was to explore the various modes of action that miR-379 has on the proliferation, migration, and invasion of human OS cells. miR-379 achieves this by targetting eukaryotic initiation factor 4GII (EIF4G2). Human OS cell lines U2OS and MG-63 were selected and assigned into blank, miR-379 mimics, miR-379 mimic negative control (NC), miR-379 inhibitors, miR-379 inhibitor NC, EIF4G2 shRNA, control shR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…Deregulation of miRNAs has been demonstrated to contribute to cancer progression . In the current study, we paid attention to miR‐379, which has been observed in non‐small cell lung cancer, cervical cancer, breast cancer, and osteosarcoma . Nevertheless, no report on the biological roles of miR‐379 alterations in laryngeal carcinoma has been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deregulation of miRNAs has been demonstrated to contribute to cancer progression . In the current study, we paid attention to miR‐379, which has been observed in non‐small cell lung cancer, cervical cancer, breast cancer, and osteosarcoma . Nevertheless, no report on the biological roles of miR‐379 alterations in laryngeal carcinoma has been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…26 In the current study, we paid attention to miR-379, which has been observed in non-small cell lung cancer, cervical cancer, breast cancer, and osteosarcoma. [16][17][18][19] Nevertheless, no report on the biological roles of miR-379 alterations in laryngeal carcinoma has been characterized. We focused on miR-379 as a candidate anti-oncogene in laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 They have the potential to regulate various critical biological processes including proliferation, migration and apoptosis of different kind of cancer cells. 25,26 Previous studies have indicated that many miRNAs, such as miR-19a, 27 miR-610, 28 CXCR4 is a well-studied G-protein coupled chemokine receptor and commonly expressed on lots of cell types including osteosarcoma cells. 34 The binding of SDF-1 to CXCR4 results in divergent downstream signaling pathways that mediate cell proliferation, migration and apoptosis.…”
Section: Discussionmentioning
confidence: 99%